2010
DOI: 10.3171/2010.5.focus10149
|View full text |Cite
|
Sign up to set email alerts
|

Update on the natural history of cavernous malformations and factors predicting aggressive clinical presentation

Abstract: Cavernous malformations (CMs) are angiographically occult, low-pressure neurovascular lesions with distinct imaging and clinical characteristics. They present with seizure, neurological compromise due to lesion hemorrhage or expansion, or as incidental findings on neuroimaging studies. Treatment options include conservative therapy, medical management of seizures, surgical intervention for lesion resection, and in select cases stereotactic radiosurgery. Optimal management requires a thorough understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
95
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(108 citation statements)
references
References 60 publications
(87 reference statements)
4
95
0
9
Order By: Relevance
“…33 In this subpopulation asymptomatic hemorrhage rates were reported to be as high as 13% per patient-year. 35 This elevated rate increases the importance of identifying familial CMs perhaps with new MR imaging sequences such as susceptibilityweighted imaging.…”
Section: Risk Of Hemorrhagementioning
confidence: 90%
See 1 more Smart Citation
“…33 In this subpopulation asymptomatic hemorrhage rates were reported to be as high as 13% per patient-year. 35 This elevated rate increases the importance of identifying familial CMs perhaps with new MR imaging sequences such as susceptibilityweighted imaging.…”
Section: Risk Of Hemorrhagementioning
confidence: 90%
“…Earlier population studies retrospectively reviewing MR imaging documented symptomatic hemorrhage rates between 0.25% and 2.3% per patient-year and about 0.1%-1.4% per lesion-year. 9,28,33 However, many of these rates were calculated assuming that the CMs were present at birth, and the risk of hemorrhage was calculated considering a patient's entire lifespan. Prospective studies have demonstrated a rate of hemorrhage between 0.8% and 3.8% per patient-year.…”
Section: Risk Of Hemorrhagementioning
confidence: 99%
“…The number of patients presenting with hemorrhage ranges from 20 to 57% (8,9,26). The risk of bleeding is influenced by many factors as deep anatomical location, female sex, pregnancy, brain radiotherapy, familial and multiple form of disease (11,18,21,22).…”
Section: Discussionmentioning
confidence: 99%
“…MRI is used for the diagnosis, especially in T2 WI (6). The clinical presentation may vary from asymptomatic forms, estimated to be 2-32%, intracranial hemorrhage or seizures (1,(24)(25)(26).…”
mentioning
confidence: 99%
“…Developmental venous anomalies themselves have a very low risk of hemorrhage, with prospective series reporting a symptomatic hemorrhage rate as low as 0.3% [221]. They are, however, associated with the development of other vascular malformations (in particular cavernous malformation), which increase the risk of symptomatic hemorrhage to as high as 6% per year [227].…”
Section: Prognosismentioning
confidence: 99%